2018
DOI: 10.1051/matecconf/201823002003
|View full text |Cite
|
Sign up to set email alerts
|

Bearing capacity of RC beams reinforced with high strength rebars and steel plate

Abstract: Nowadays, reducing the material content of not only buildings and structures in general, but also individual constructions is a topical task that can be realized through the use of high-strength concrete and reinforcement, as well as with the use of external reinforcement. The concentrated location of sheet reinforcement on the external the most tense facets of steel and concrete structures increases the operating height of the cross-section, makes it possible to more effectively use the strength properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 9 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Thus, it was found that corrosion of reinforcement occurs in all cracks with an opening over 0.05 mm with the possibility of its amplification, when the opening width increases. By providing structural measures of crack resistance of reinforced concrete structures, it is possible to achieve a crack opening width of 0.05 mm directly before failure [ 18 ], which protects the metal from the inside from corrosion.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Thus, it was found that corrosion of reinforcement occurs in all cracks with an opening over 0.05 mm with the possibility of its amplification, when the opening width increases. By providing structural measures of crack resistance of reinforced concrete structures, it is possible to achieve a crack opening width of 0.05 mm directly before failure [ 18 ], which protects the metal from the inside from corrosion.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The RC constructions are mostly useful at the world [1][2][3][4][5]. However, there are some disadvantages of this constructions [6][7][8][9][10][11][12]. In this case, are a lot of researching for strengthening this constructions [13], also for improving shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…This material has found its application in production and in a constructional engineering (Brózda et al, 2017;Mazur, 2016). In structural elements, subjected to compression with bending, compressive stresses are taken by concrete while tensile stresses are transmitted to the rebar (Bobalo et al, 2018;Krainskyi et al, 2018b). At the same time, concrete serves as protection of structures from corrosion and various damages.…”
Section: Introductionmentioning
confidence: 99%